Lithium manganese iron phosphate precursor, preparation method thereof and application thereof
Patent Information
- Application Number
- CN202610955011.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]现有固相法合成磷酸锰铁锂正极材料时,铁、锰、磷、锂等元素依赖机械混合,无法实现均匀分布,导致正极材料电化学性能波动,制备得到的正极活性材料的均一性和稳定性较差,进而导致正极活性材料的电化学性能(如倍率性能、循环稳定性)波动较大,影响磷酸锰铁锂正极活性材料的应用
[0038]本发明提供的磷酸锰铁锂前驱体用于制备正极活性材料,能够显著提升正极活性材料的产品稳定性和均一性。本发明提供的磷酸锰铁锂前驱体由磷酸锂与磷酸氢铁锰水合物复合而成,其用于制备正极活性材料时能够显著提升产品稳定性和均一性,磷酸锂作为高熔点、高化学稳定性的锂源,在制备正极活性材料过程中能够均匀地熔融并渗透至磷酸氢铁锰水合物分解形成的多孔骨架中,避免了局部锂过量或不足导致的杂相生成;同时,磷酸氢铁锰水合物在热分解过程中释放结晶水和结构水,形成具有丰富孔隙和高度反应活性的中间体,该中间体与磷酸锂在分子水平上实现均匀混合与原位反应,从而有效抑制了颗粒的异常长大和成分偏析;此外,磷酸锂与磷酸氢铁锰水合物之间良好的界面相容性,使得制备正极活性材料过程中锂离子能够有序地嵌入橄榄石结构,形成结晶度高、晶格缺陷少、元素分布均匀的磷酸锰铁锂正极材料,最终显著提升了正极活性材料的产品稳定性。
Smart Images

Figure CN122897378A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary batteries, and more particularly to a lithium manganese iron phosphate precursor, its preparation method, and its application. Background Technology
[0002] Lithium manganese iron phosphate (LiMnFePO4) cathode material is an important research direction in the field of lithium-ion batteries. It is widely used in new energy vehicles, energy storage systems, consumer electronics (such as smartphones and laptops), and power tools, where there are strict requirements for high energy density, long cycle life, and high safety.
[0003] In the existing solid-state synthesis of lithium manganese iron phosphate cathode materials, elements such as iron, manganese, phosphorus, and lithium rely on mechanical mixing, which cannot achieve uniform distribution. This leads to fluctuations in the electrochemical performance of the cathode material, poor uniformity and stability of the prepared cathode active material, and consequently, large fluctuations in the electrochemical performance (such as rate performance and cycle stability) of the cathode active material, affecting the application of lithium manganese iron phosphate cathode active materials.
[0004] From the perspective of precursors, developing lithium manganese iron phosphate precursors that can improve product stability and uniformity will promote the further development of lithium manganese iron phosphate cathode active materials. Summary of the Invention
[0005] This invention provides a lithium manganese iron phosphate precursor, and lithium manganese iron phosphate cathode materials prepared using this precursor exhibit excellent product stability and uniformity.
[0006] This invention provides a method for preparing a lithium manganese iron phosphate precursor. The lithium manganese iron phosphate precursor prepared by this method can be used to prepare a lithium manganese iron phosphate cathode material, which has excellent product stability and uniformity.
[0007] This invention provides a positive electrode active material, which is prepared using the above-mentioned lithium manganese iron phosphate precursor and has excellent stability and uniformity.
[0008] The present invention provides a positive electrode sheet comprising the above-mentioned positive electrode active material, which has excellent ion-electron conductivity, energy density and rate performance.
[0009] The present invention provides a battery comprising the above-mentioned positive electrode sheet, which has excellent ion-electron conductivity, energy density and rate performance.
[0010] One aspect of this invention provides a lithium manganese iron phosphate precursor, comprising lithium phosphate and manganese iron hydrogen phosphate hydrate.
[0011] The lithium manganese iron phosphate precursor described above, wherein the iron manganese hydrogen phosphate hydrate comprises (Fe aMn b )5H2(PO4)4•4H2O、(Fe x Mn y At least one of HPO4•cH2O, wherein a:b is 1:9~9:1, x:y is 1:9~9:1, and 0<c≤3;
[0012] The lithium manganese iron phosphate precursor described above further includes iron manganese hydrogen phosphate, the chemical formula of which is (Fe... e Mn f HPO4, where e:f is 1:9 to 9:1.
[0013] The lithium manganese iron phosphate precursor described above has a loose pack density of A, 0.8 g / cm³. 3 ≤A≤1.5g / cm 3 ;
[0014] And / or, the tap density of the lithium manganese iron phosphate precursor is B, 1.5 g / cm³. 3 ≤B≤2.5g / cm 3 .
[0015] The lithium manganese iron phosphate precursor described above includes lithium phosphate, (Fe) a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y HPO4•cH2O, a:b is 1:9~9:1, x:y is 1:9~9:1, 0<c≤3;
[0016] The Li3PO4, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y The molar ratio of HPO4•cH2O is (1.5~56):(2~48):(0.1~96.5).
[0017] The lithium manganese iron phosphate precursor described above includes lithium phosphate, (Fe) a Mn b )5H2(PO4)4•4H2O、(Fe e Mn f HPO4, a:b ratio is 1:9 to 9:1, e:f ratio is 1:9 to 9:1;
[0018] The lithium phosphate, (Fe a Mn b)5H2(PO4)4•4H2O、(Fe e Mn f The molar ratio of HPO4 is (1.5~56):(2~48):(0.1~96.5).
[0019] The lithium manganese iron phosphate precursor described above is prismatic in shape, with an average width of 100-500 nm for its cross-section and an average length of 100-1000 nm.
[0020] And / or, the specific surface area of the lithium manganese iron phosphate precursor is ≤20m². 2 / g.
[0021] The lithium manganese iron phosphate precursor described above has a (Mn+Fe) / P ratio of (0.955~0.985):1 and a Li / P ratio of (1.01~1.06):1.
[0022] In another aspect, the present invention provides a method for preparing the lithium manganese iron phosphate precursor as described above, comprising the following steps:
[0023] 1) The first mixed system, including a lithium source and a first phosphorus source, is subjected to a first coprecipitation treatment to obtain an intermediate;
[0024] 2) Perform a second coprecipitation treatment on the second mixed system including the intermediate, the second phosphorus source, the manganese source, and the iron source to obtain the lithium manganese iron phosphate precursor.
[0025] In the preparation method described above, the solid content of the first mixed system is 15%~30%;
[0026] And / or, the solid content of the second mixture is 5% to 15%;
[0027] And / or, the pH of the first coprecipitation treatment is 5-8;
[0028] And / or, the pH of the second coprecipitation treatment is 4 to 9.
[0029] In the preparation method described above, the temperature of the first coprecipitation treatment is 40~90℃ and the time is 1~6h;
[0030] And / or, the temperature of the second coprecipitation treatment is 40~90℃, and the time is 1~6h.
[0031] In the preparation method described above, the molar ratio of the lithium source and the first phosphorus source is (2~3):1;
[0032] And / or, the molar ratio of the metal salt to the second phosphorus source is (1.5~2):1; the metal salt includes the manganese source and the iron source;
[0033] And / or, the molar ratio of the manganese source and the iron source is (7:3) to (5:5).
[0034] In another aspect, the present invention provides a positive electrode active material, which is prepared using the lithium manganese iron phosphate precursor as described above;
[0035] Alternatively, it can be prepared using the lithium manganese iron phosphate precursor obtained by the preparation method described above.
[0036] In another aspect, the present invention provides a positive electrode sheet, including a positive electrode active layer, wherein the positive electrode active material includes the positive electrode active material as described above.
[0037] In another aspect, the present invention provides a battery comprising the positive electrode sheet as described above.
[0038] The lithium manganese iron phosphate precursor provided by this invention is used to prepare positive electrode active materials, which can significantly improve the product stability and uniformity of positive electrode active materials. The lithium manganese iron phosphate precursor provided by this invention is composed of lithium phosphate and manganese iron hydrogen phosphate hydrate. When used to prepare cathode active materials, it can significantly improve product stability and uniformity. As a lithium source with a high melting point and high chemical stability, lithium phosphate can uniformly melt and penetrate into the porous framework formed by the decomposition of manganese iron hydrogen phosphate hydrate during the preparation of cathode active materials, avoiding the formation of impurity phases caused by local lithium excess or deficiency. At the same time, manganese iron hydrogen phosphate hydrate releases crystal water and structural water during thermal decomposition, forming an intermediate with abundant porosity and high reactivity. This intermediate and lithium phosphate achieve uniform mixing and in-situ reaction at the molecular level, thereby effectively inhibiting abnormal particle growth and component segregation. In addition, the good interfacial compatibility between lithium phosphate and manganese iron hydrogen phosphate hydrate allows lithium ions to be orderly embedded in the olivine structure during the preparation of cathode active materials, forming a lithium manganese iron phosphate cathode material with high crystallinity, few lattice defects, and uniform element distribution, ultimately significantly improving the product stability of the cathode active material. Attached Figure Description
[0039] Figure 1 The XRD pattern of the lithium manganese iron phosphate precursor provided in Example 1 of this invention;
[0040] Figure 2 The XRD pattern of the lithium manganese iron phosphate precursor provided in Comparative Example 1 of this invention;
[0041] Figure 3 This is a SEM image of the lithium manganese iron phosphate precursor provided in Example 1 of the present invention;
[0042] Figure 4 This is a SEM image of the lithium manganese iron phosphate precursor provided in Comparative Example 1 of the present invention.
[0043] Figure 5 The XRD pattern of the positive electrode active material prepared using the lithium manganese iron phosphate precursor provided in Example 1 is shown below.
[0044] Figure 6 This is a SEM image of the positive electrode active material prepared using the lithium manganese iron phosphate precursor provided in Example 1 of this invention. Detailed Implementation
[0045] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numerals in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Rather, they are merely examples of apparatuses and methods consistent with some aspects of the invention as detailed in the appended claims.
[0046] The preparation of existing lithium manganese iron phosphate cathode materials mainly employs a solid-state method. The core steps include mixing iron (e.g., FeSO4), manganese (e.g., MnSO4), phosphorus (e.g., H3PO4), and lithium (e.g., Li2CO3) in a specific ratio, followed by high-temperature sintering (typically 700–900℃) to generate the target product. This method relies on mechanical mixing to achieve elemental distribution, but it suffers from the following problems: Insufficient elemental mixing uniformity: Existing solid-state methods cannot achieve uniform distribution of iron, manganese, phosphorus, and lithium at the atomic scale, leading to fluctuations in the electrochemical performance of the cathode material. Difficulty in precisely controlling elemental ratios: The co-precipitation efficiency of iron and manganese is low, easily causing the elemental ratio to deviate from the target value, inducing the formation of impurity phases. This limits the stability and uniformity of subsequent cathode active materials, thus affecting the compaction density and optimization of electrochemical performance.
[0047] Starting from the shortcomings of existing technologies and addressing the problem of uneven element mixing, the inventors proposed a lithium manganese iron phosphate precursor that can provide lithium, iron, manganese and phosphorus. By controlling the proportion of various elements in the lithium manganese iron phosphate precursor and the loose packing density of the lithium manganese iron phosphate precursor, the stability and uniformity of subsequent positive electrode active materials can be improved.
[0048] Based on this, the present invention provides a lithium manganese iron phosphate precursor, comprising lithium phosphate and manganese iron hydrogen phosphate hydrate.
[0049] Among them, iron-manganese hydrogen phosphate hydrate refers to the mixture of iron (Fe), manganese (Mn), and phosphate (PO4). 3- ), hydrogen ions (H) + Salt hydrates are composed of ions and water of crystallization (H2O).
[0050] The composition of lithium manganese iron phosphate precursors can be detected using common detection methods in the field, such as XRD to detect the type of substance.
[0051] Specifically, the lithium manganese iron phosphate precursor is a solid solution formed by the aggregation of lithium phosphate and manganese hydrogen phosphate hydrate.
[0052] The lithium manganese iron phosphate precursor provided by this invention is used to prepare positive electrode active materials, which can significantly improve the product stability and uniformity of positive electrode active materials. The lithium manganese iron phosphate precursor provided by this invention is composed of lithium phosphate and manganese iron hydrogen phosphate hydrate. When used to prepare cathode active materials, it can significantly improve product stability and uniformity. As a lithium source with a high melting point and high chemical stability, lithium phosphate can uniformly melt and penetrate into the porous framework formed by the decomposition of manganese iron hydrogen phosphate hydrate during the preparation of cathode active materials, avoiding the formation of impurity phases caused by local lithium excess or deficiency. At the same time, manganese iron hydrogen phosphate hydrate releases crystal water and structural water during thermal decomposition, forming an intermediate with abundant porosity and high reactivity. This intermediate and lithium phosphate achieve uniform mixing and in-situ reaction at the molecular level, thereby effectively inhibiting abnormal particle growth and component segregation. In addition, the good interfacial compatibility between lithium phosphate and manganese iron hydrogen phosphate hydrate allows lithium ions to be orderly embedded in the olivine structure during the preparation of cathode active materials, forming a lithium manganese iron phosphate cathode material with high crystallinity, few lattice defects, and uniform element distribution, ultimately significantly improving the product stability of the cathode active material.
[0053] In some embodiments of the present invention, iron-manganese hydrogen phosphate hydrate includes (Fe a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y At least one of HPO4•cH2O, wherein a:b is 1:9~9:1, x:y is 1:9~9:1, and 0<c≤3.
[0054] The composition of lithium manganese iron phosphate precursors can be detected using common detection methods in the field, such as XRD to detect the type of substance and inductively coupled plasma mass spectrometry to detect the elemental ratio.
[0055] In detail, a:b includes, but is not limited to, a range consisting of 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, or any two of these ranges; x:y includes, but is not limited to, a range consisting of 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, or any two of these ranges; and c includes, but is not limited to, a range consisting of 0.5, 1, 1.5, 2, 2.5, 3, or any two of these ranges.
[0056] When the hydrated iron-manganese hydrogen phosphate meets the above conditions, it means that the lithium iron manganese phosphate precursor has a precise hydrated acid salt structure. During the subsequent sintering process, the gradual removal of structural water and structural hydrogen can form a uniform porous framework, providing sufficient channels and active sites for lithium ion diffusion and in-situ reaction, thereby significantly improving sintering efficiency and product crystallinity. Moreover, the phase corresponding to this chemical formula has high purity and few lattice defects. After being combined with lithium phosphate, it can achieve uniform mixing at the molecular level, effectively suppressing the generation of impurity phases and component segregation, and ultimately significantly improving the product stability and uniformity of the positive electrode active material. At the same time, the iron-manganese ratio is adjustable in a wide range of 1:9 to 9:1, which allows the manganese content of the final lithium iron manganese phosphate positive electrode material to be flexibly controlled according to application requirements.
[0057] (Fe x Mn y HPO4•cH2O and Li3PO4, (Fe a Mn b The synergistic effect of 5H2(PO4)4•4H2O can further optimize the microstructure and packing mode of precursor particles. (Fe x Mn y HPO4•cH2O helps to form more regular and denser primary particles, thereby effectively improving the loose packing density and tapped density of the precursor on a macroscopic scale.
[0058] In some embodiments, the lithium manganese iron phosphate precursor further includes manganese iron hydrogen phosphate, the chemical formula of which is (Fe e Mn f HPO4, where e:f is 1:9 to 9:1.
[0059] Iron manganese hydrogen phosphate refers to a mixture of iron (Fe), manganese (Mn), and phosphate (PO4). 3- ), hydrogen ions (H) + These are salt compounds composed of [various components]. In some embodiments of the present invention, the loose packing density of the lithium manganese iron phosphate precursor is A, 0.8 g / cm³. 3 ≤A≤1.5g / cm 3 .
[0060] The loose packing density of lithium manganese iron phosphate precursor can be determined using methods commonly used in the field, such as according to the provisions of the national standard GB / T1479.1-2011 "Metal powders - Determination of loose packing density - Part 1: Funnel method".
[0061] Specifically, the loose pack density of the lithium manganese iron phosphate precursor includes, but is not limited to, 0.8 g / cm³. 3 0.85g / cm 3 0.9g / cm3 1.0g / cm 3 1.1g / cm 3 1.2g / cm 3 1.3g / cm 3 1.4g / cm 3 1.5g / cm 3 Or the range formed by any two of them.
[0062] When the loose packing density is not less than 0.8 g / cm³ 3 At this stage, the lithium manganese iron phosphate precursor particles are tightly packed, resulting in a high content of active material per unit volume. This effectively reduces interparticle porosity and sintering shrinkage during subsequent sintering to prepare the cathode active material, thereby obtaining lithium manganese iron phosphate cathode materials with high tap density and high pressure tap density, which is beneficial for improving the volumetric energy density of the battery. When the loose packing density does not exceed 1.5 g / cm³... 3 At the same time, the lithium manganese iron phosphate precursor still maintains sufficient porosity and specific surface area, providing the necessary space for lithium source penetration, gas discharge and grain growth during sintering, avoiding the inhibition of reaction kinetics and abnormal grain growth caused by excessive densification, thereby significantly improving the product stability and uniformity of the positive electrode active material.
[0063] In some embodiments of the present invention, the tap density of the lithium manganese iron phosphate precursor is B, 1.5 g / cm³. 3 ≤B≤2.5g / cm 3 .
[0064] The tap density of lithium manganese iron phosphate precursor can be detected using common testing methods in the field, such as in accordance with GB / T 5162-2021 "Determination of Tap Density of Metal Powders".
[0065] Specifically, the tap density of the lithium manganese iron phosphate precursor includes, but is not limited to, 1.5 g / cm³. 3 1.55g / cm 3 1.6g / cm 3 1.7g / cm 3 1.8g / cm 3 1.9g / cm 3 2.0g / cm 3 2.1g / cm 3 2.2g / cm 3 2.3g / cm 3 2.4g / cm 3 2.5g / cm 3 Or the range formed by any two of them.
[0066] When the tap density of the lithium manganese iron phosphate precursor is within the above range, it means that lithium manganese iron phosphate has excellent particle size distribution and dense filling ability. In the process of preparing positive electrode active materials, the lithium manganese iron phosphate precursor can carry out solid-phase reaction with closer contact, promote mass transport and grain growth, thereby obtaining a more compact positive electrode active material with fewer grain boundaries. Moreover, the high tap density of the lithium manganese iron phosphate precursor can be directly converted into the high tap density of the final positive electrode active material, which allows more active material to be filled in the limited space of the battery, greatly improving the volumetric energy density of the battery. At the same time, the dense and fluid lithium manganese iron phosphate precursor also greatly improves the coating process window of the positive electrode slurry and the consistency of the electrode sheet, improving the production yield and battery cycle stability.
[0067] In some embodiments of the present invention, the lithium manganese iron phosphate precursor includes lithium phosphate, (Fe) a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y HPO4•cH2O, a:b is 1:9~9:1, x:y is 1:9~9:1, 0<c≤3; Li3PO4, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y The molar ratio of HPO4•cH2O is (1.5~56):(2~48):(0.1~96.5).
[0068] The molar ratios of various substances in lithium manganese iron phosphate precursors can be detected using methods commonly used in the field, such as the Rietveld full-spectrum refined quantitative analysis method based on X-ray diffraction (XRD) data.
[0069] In detail, Li3PO4, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y The molar ratio of HPO4•cH2O includes, but is not limited to, 1.5:2:96.5, 30:2:68, 56:2:42, 1.5:20:78.5, 1.5:48:50.5, 52:47.9:0.1, or any combination thereof.
[0070] When Li3PO4, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe x Mn yWhen the molar ratio of HPO4•cH2O is within the above range, it is possible to achieve a better uniform distribution of Li, Fe, Mn and P at the atomic level, resulting in lithium manganese iron phosphate cathode material with higher compositional uniformity and structural stability, thereby improving the cycle stability and rate performance of the battery.
[0071] In some embodiments, lithium phosphate, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y The molar ratio of HPO4•cH2O is (40~56):(30~48):(0.1~20).
[0072] This optimized range allows for more precise control of the solid-state reaction kinetics and crystallization process of the precursor system. It not only further ensures a highly uniform atomic distribution of lithium, iron, manganese, and phosphorus, but also, when the three are in the aforementioned ratio, controls the (Mn+Fe) / P ratio to reach (0.955~0.985):1. This effectively suppresses phase separation or impurity phase formation caused by fluctuations in the manganese-iron ratio, and significantly enhances the crystal structure stability of the material. This further enables the precursor to achieve a superior discharge specific capacity when converted into lithium manganese iron phosphate cathode material in subsequent processes.
[0073] In some embodiments, the lithium manganese iron phosphate precursor includes lithium phosphate, (Fe) a Mn b )5H2(PO4)4•4H2O、(Fe e Mn f HPO4, a:b is 1:9~9:1, x:y is 1:9~9:1, e:f is 1:9~9:1;
[0074] Lithium phosphate, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe e Mn f The molar ratio of HPO4 is (1.5~56):(2~48):(0.1~96.5).
[0075] When Li3PO4, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe e Mn f When the molar ratio of HPO4 is within the above range, it is possible to achieve a better uniform distribution of Li, Fe, Mn and P at the atomic level, resulting in lithium manganese iron phosphate cathode material with higher compositional uniformity and structural stability, thereby improving the cycle stability and rate performance of the battery.
[0076] In some embodiments, lithium phosphate, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe e Mn f The molar ratio of HPO4 is (40~56): (30~48): (0.1~20).
[0077] This preferred range allows for more precise control of the solid-state reaction kinetics and crystallization process of the precursor system. It not only further ensures a highly uniform distribution of lithium, iron, manganese, and phosphorus at the atomic level, but also, when the three are in the above-mentioned ratio, controls the (Mn+Fe) / P ratio to reach (0.955~0.985):1, effectively suppressing phase separation or impurity phase formation caused by fluctuations in the manganese-iron ratio. It also significantly enhances the crystal structure stability of the material, further enabling the precursor to achieve a superior discharge specific capacity when converted into lithium manganese iron phosphate cathode material in subsequent processes. In some embodiments of the present invention, the lithium manganese iron phosphate precursor is prismatic, with an average width of 100~500 nm for its cross-section and an average length of 100~1000 nm.
[0078] The morphology, cross-sectional diameter, and length of lithium manganese iron phosphate precursors can be detected using methods commonly used in the field, such as scanning electron microscopy. The cross-sectional diameter can be determined by cross-sectional processing of the lithium manganese iron phosphate precursor.
[0079] In this invention, the average width and average length of the cross section refer to the average value of the width obtained by detecting the lithium manganese iron phosphate precursor in the field of view using a scanning electron microscope at 50,000x magnification, while the average value of the length obtained refers to the average value of the detected length.
[0080] Scanning electron microscopy revealed that the lithium manganese iron phosphate precursor provided by this invention is prismatic, meaning that the lithium manganese iron phosphate precursor has a columnar shape and its sides are surrounded by multiple planes (i.e., facets).
[0081] The cross-sectional width of the lithium manganese iron phosphate precursor refers to the width of the cross section perpendicular to the length direction of the prismatic particles.
[0082] The average width of the cross section of the lithium manganese iron phosphate precursor includes, but is not limited to, a range of 100nm, 200nm, 300nm, 400nm, 500nm, or any two of these ranges; the average length of the lithium manganese iron phosphate precursor includes, but is not limited to, a range of 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, or any two of these ranges.
[0083] When the morphology and size of the lithium manganese iron phosphate precursor meet the above range, on the one hand, the packing density and fluidity of the precursor are increased, which is beneficial to the uniform coating of the subsequent cathode material slurry and electrode preparation; on the other hand, the anisotropic prismatic morphology provides a regular template and sufficient reaction interface for the subsequent preparation of cathode active materials, which helps to promote the uniform insertion / extraction of lithium ions and effectively buffer the volume strain during the charging and discharging process, thereby ultimately improving the tap density, structural stability and rate performance of the prepared lithium manganese iron phosphate cathode material.
[0084] In some embodiments of the present invention, the specific surface area of the lithium manganese iron phosphate precursor is ≤20m². 2 / g.
[0085] The specific surface area of lithium manganese iron phosphate precursors can be detected using methods commonly used in the field, such as nitrogen adsorption-desorption.
[0086] Specifically, the specific surface area of the lithium manganese iron phosphate precursor includes, but is not limited to, 20 m² / g. 2 / g、18m 2 / g、17m 2 / g, 16m 2 / g, 15m 2 / g、14m 2 / g、13m 2 / g or any of them ≤20m 2 The range of / g.
[0087] In some embodiments of the present invention, the specific surface area of the lithium manganese iron phosphate precursor is ≥3m². 2 / g.
[0088] The lower specific surface area effectively reduces the surface energy of the particles, significantly improving the physicochemical stability of the precursor during storage and processing, and suppressing the tendency of moisture absorption and agglomeration. In the subsequent sintering process, this characteristic is conducive to achieving more uniform and controllable solid-phase reaction kinetics, promoting the formation of a well-crystallized and dense cathode active material, and improving the uniformity and stability of the cathode active material.
[0089] In some embodiments of the present invention, the (Mn+Fe) / P ratio in the lithium manganese iron phosphate precursor is (0.955~0.985):1, and the Li / P ratio is (1.01~1.06):1.
[0090] In this invention, (Mn+Fe) / P refers to the ratio of the sum of the molar amounts of manganese and iron to the molar amount of phosphorus in the lithium manganese iron phosphate precursor, while Li / P refers to the molar ratio of lithium to phosphorus in the lithium manganese iron phosphate precursor.
[0091] It is understood that the lithium manganese iron phosphate precursor provided by the present invention may include other types of lithium-containing compounds, such as lithium carbonate, in addition to lithium phosphate and manganese iron hydrogen phosphate hydrate.
[0092] Common methods in this field can be used to detect the molar ratio relationships between various elements, such as inductively coupled plasma mass spectrometry (ICP-MS).
[0093] In detail, (Mn+Fe) / P includes, but is not limited to, a range of 0.955:1, 0.960:1, 0.965:1, 0.970:1, 0.975:1, 0.980:1, 0.985:1, or any two of these ranges; Li / P includes, but is not limited to, a range of 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, or any two of these ranges.
[0094] The moderately low (Mn+Fe) / P design effectively suppresses the reduction of transition metals and the formation of impurity phases (such as Fe2P) during high-temperature sintering, ensuring the structural stability of the lithium manganese iron phosphate precursor; while the moderately high Li / P design fully compensates for the lithium volatilization loss during sintering, ensuring that the final product has a suitable degree of lithiation.
[0095] In another aspect, the present invention provides a method for preparing the lithium manganese iron phosphate precursor as described above, comprising the following steps:
[0096] 1) The first mixed system, including a lithium source and a first phosphorus source, is subjected to a first coprecipitation treatment to obtain an intermediate;
[0097] 2) The second mixed system, including the intermediate, the second phosphorus source, the manganese source, and the iron source, is subjected to a second coprecipitation treatment to obtain the lithium manganese iron phosphate precursor.
[0098] The preparation method provided by the present invention prepares a lithium manganese iron phosphate precursor, which includes lithium phosphate and manganese iron hydrogen phosphate hydrate.
[0099] Specifically, in step 1), a first coprecipitation treatment is performed on a first mixed system comprising a lithium source, a first phosphorus source, and an aqueous solution to obtain an intermediate lithium phosphate with a high bulk density.
[0100] In some embodiments of the present invention, a lithium source solution of a certain concentration and a first phosphorus source solution of a certain concentration can be prepared in advance. For example, the concentration of the lithium source solution is 0.1~6 mol / L and the concentration of the first phosphorus source solution is 0.1~16 mol / L.
[0101] This invention does not limit the specific types of lithium source and first phosphorus source. Common lithium source and first phosphorus source in the art can be selected. For example, the lithium source may include at least one of lithium sulfate, lithium chloride, lithium nitrate, lithium acetate, lithium hydroxide, and lithium carbonate; the first phosphorus source may include at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, trisodium phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, tripotassium phosphate, and lithium dihydrogen phosphate.
[0102] In step 2), the second mixed system, which includes intermediate lithium phosphate, second phosphorus source, manganese source and iron source, is subjected to a second coprecipitation treatment. During the second coprecipitation treatment, ferrous phosphate and manganese phosphate are precipitated with lithium phosphate as template to obtain lithium manganese iron phosphate precursor.
[0103] This invention does not limit the type of the second phosphorus source, manganese source, and iron source, and can use common second phosphorus sources, manganese sources, and iron sources in the art. For example, the second phosphorus source may include at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, trisodium phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, tripotassium phosphate, and lithium dihydrogen phosphate; the manganese source may include at least one of manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate; and the iron source may include at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, and ferrous acetate.
[0104] In some embodiments, a second phosphorus source solution, a manganese source solution, and an iron source solution of a certain concentration can be prepared in advance. For example, a second phosphorus source solution of 0.1~16 mol / L, a manganese source solution of 0.1~3 mol / L, and an iron source solution of 0.1~3 mol / L can be prepared.
[0105] It is understandable that, in order to remove impurities during the co-precipitation process and maintain a suitable moisture content in the lithium manganese iron phosphate precursor, washing and drying can be performed after the second co-precipitation treatment.
[0106] The present invention does not limit the washing liquid used for washing, and common washing liquids can be selected, such as a 0.1~0.2 mol / L lithium phosphate mixed solution.
[0107] The present invention does not limit the drying process parameters, and appropriate parameters can be selected according to the actual situation, such as 60~200℃.
[0108] This invention employs a stepwise co-precipitation process. By pre-reacting a lithium source with a first phosphorus source to generate an intermediate, and then co-precipitating this intermediate with a second phosphorus source, a manganese source, and an iron source, a second co-precipitation process is performed. This effectively achieves uniform mixing of various elements, thereby improving the uniformity and stability of the positive electrode active material. Due to the large solubility product constant and relatively high solubility of lithium phosphate, its nucleation and growth process in solution can be easily controlled by adjusting the solid content to achieve morphology control. In the first co-precipitation stage, lithium and the first portion of phosphorus preferentially form a lithium phosphate intermediate with a prismatic growth habit and high loose packing density. This intermediate, possessing both high loose packing density and specific exposed crystal faces, acts as a template in the second co-precipitation stage. Driven by the lattice induction and surface energy reduction effect of the template surface, the manganese source, the iron source, and the second portion of phosphorus undergo directional deposition and growth along the prismatic contour of the intermediate, ensuring that the obtained phosphate product fully retains the high loose packing density prismatic structure characteristics of the template. Ultimately, lithium, iron, manganese, and phosphorus achieve a highly uniform atomic-level distribution within and between particles. In the subsequent high-temperature sintering preparation of positive electrode active materials, it can promote the synchronous and orderly insertion of various elements into the lattice, reduce lattice defects and compositional fluctuations, thereby significantly improving the electrochemical consistency, cycle stability and rate performance of the positive electrode material.
[0109] In some embodiments of the present invention, the solid content of the first mixed system is 15% to 30%.
[0110] In this invention, the solid content of the first mixed system refers to the percentage of solid matter in the first mixed system by mass, calculated as (mass of lithium source + mass of first phosphorus source) / mass of the first mixed system.
[0111] In detail, the solid content of the first mixture system includes, but is not limited to, a range of 15%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, or any two of these.
[0112] Lithium phosphate has a high solubility product constant (Ksp) and a high nucleation barrier. Therefore, in the first coprecipitation stage, the solid content is controlled at 15%~30% to maintain a high supersaturation in the reaction system, promoting rapid and uniform nucleation of the lithium source and the first phosphorus source. This generates a large number of uniform, regular, and dense nanoscale lithium-containing intermediate particles. These intermediates are then uniformly combined with iron-manganese phosphate hydrate in the subsequent second coprecipitation process, resulting in unobstructed lithium-ion diffusion channels and low grain boundary resistance in the final lithium iron phosphate cathode material. If the solid content is less than 15%, the system is too thin, and the lithium phosphate particles are excessively dispersed and have a small particle size, making them prone to agglomeration during subsequent sintering, leading to increased resistivity in local lithium-rich areas. If the solid content is greater than 30%, the system viscosity is too high, and the lithium phosphate particles are prone to agglomeration or incomplete coating, forming defective areas with uneven lithium distribution, increasing interfacial impedance and lattice distortion, thereby significantly increasing the overall resistivity of the material.
[0113] In some embodiments of the present invention, the solid content of the second mixture is 5% to 15%.
[0114] In this invention, the solid content of the second mixture refers to the percentage of solid matter in the second mixture by mass, calculated as (mass of intermediate + mass of second phosphorus source + mass of manganese source + mass of iron source) / mass of the second mixture.
[0115] The solid content of the second mixture system includes, but is not limited to, 5%, 6%, 8%, 10%, 12%, 14%, 15%, or any combination thereof.
[0116] The Ksp of iron-manganese hydrogen phosphate hydrate is relatively small, resulting in a low nucleation barrier. Therefore, in the second co-precipitation stage, the solid content is controlled at 5%~15% to maintain a low degree of supersaturation in the reaction system. This allows the iron-manganese phosphate to undergo orderly, uniform, and dense epitaxial growth on the surface of the intermediate, avoiding secondary nucleation or disordered agglomeration caused by excessive local supersaturation. The final product is a lithium iron manganese phosphate precursor with a regular morphology (prismatic), smooth surface, dense interior, and pure phase. During subsequent sintering, this precursor achieves a uniform distribution of lithium, iron, manganese, and phosphorus elements at the molecular level, forming a lithium iron manganese phosphate cathode material with high crystallinity and few lattice defects, thereby effectively reducing the grain boundary resistance and charge transfer impedance of the material.
[0117] To ensure the efficiency of coprecipitation, a suitable pH range can be selected.
[0118] In some embodiments of the present invention, the pH of the first coprecipitation treatment is 5 to 8.
[0119] In detail, the pH of the first coprecipitation treatment includes, but is not limited to, a range of 5, 6, 7, 8, or any two of these.
[0120] The pH of the coprecipitation system can be controlled by adding a pH adjuster, such as sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, or ammonium bicarbonate.
[0121] When the pH of the first coprecipitation treatment is within the above-mentioned range, the nucleation and growth kinetics of the intermediate can be regulated, thereby optimizing its particle morphology, size, and reactivity. This allows the lithium and phosphorus sources to be efficiently and completely converted into uniformly structured nanoscale or amorphous precursors, while maintaining a suitable chemical state on their surface. This enables more thorough and uniform molecular-level mixing with the manganese and iron sources in the subsequent second coprecipitation step. Furthermore, when the pH of the first coprecipitation treatment is not higher than 8, it ensures that the final lithium manganese iron phosphate precursor contains (Fe...) a Mn b)5H2(PO4)4•4H2O、(Fe x Mn y The initial step involves HPO4•cH2O. If the pH value is too high, excessive OH- in the system will occur during the second coprecipitation stage. - Will seize HPO4 2- The protons on the surface promote the conversion of PO4. 3- Transformation, leading to (Fe x Mn y The structure of HPO4·CH2O collapses, and the product exists only as (Fe) a Mn b It exists as a single phase: 5H2(PO4)4·4H2O.
[0122] In some embodiments of the present invention, the pH of the second coprecipitation treatment is 4 to 9.
[0123] In detail, the pH of the second coprecipitation treatment includes, but is not limited to, a range of 4, 5, 6, 7, 8, 9, or any two of these.
[0124] The pH of the coprecipitation system can be controlled by adding a pH adjuster, such as sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, or ammonium bicarbonate.
[0125] By stabilizing the pH of the second coprecipitation treatment at 4-9, the nucleation and growth rates can be effectively controlled, thereby achieving controllable particle size, controllable BET, and controllable elemental ratios. This ensures that (Mn+Fe) / P < 0.985, avoiding the occurrence of Fe2P impurities during sintering, thus obtaining a precursor with highly uniform composition, uniform manganese and iron distribution, and moderate crystallinity.
[0126] In some embodiments of the present invention, the loose bulk density of the intermediate is C, which satisfies C≥0.8g / cm³. 3 .
[0127] The intermediate obtained in step 1) can be washed and dried, and then the bulk density can be tested.
[0128] The loose density of intermediates can be determined using common testing methods in the field. For example, the loose density of lithium manganese iron phosphate precursor intermediates can be tested according to the provisions of the national standard GB / T1479.1-2011 "Metal powders - Determination of loose density - Part 1: Funnel method".
[0129] Specifically, the bulk density of the intermediate includes, but is not limited to, 0.81 g / cm³. 3 0.85 g / cm 3 0.9 g / cm 3 0.95 g / cm 31.0 g / cm 3 1.05 g / cm 3 1.1 g / cm 3 1.15 g / cm 3 1.2 g / cm 3 Or other values greater than 0.8 g / cm 3 The range.
[0130] In some embodiments of the present invention, the loose bulk density of the intermediate is 0.8~1.5 g / cm³. 3 .
[0131] When the loose packing density of the intermediate is within the above range, it means that the intermediate is more compact and has better packing performance, resulting in higher tap density and electrode compaction density of the lithium manganese iron phosphate precursor. This not only improves the volumetric energy density of the battery, but its dense structure also reduces side reactions with the electrolyte, thereby significantly improving the long-term cycle stability of the material.
[0132] In some embodiments of the present invention, the temperature of the first coprecipitation treatment is 40~90°C and the time is 1~6h.
[0133] In detail, the temperature of the first coprecipitation treatment includes, but is not limited to, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any combination thereof, and the time includes, but is not limited to, 1h, 2h, 3h, 4h, 5h, 6h or any combination thereof.
[0134] By controlling the temperature and time of the first coprecipitation treatment, the reaction kinetics and crystallization process can be effectively regulated, ensuring the formation of intermediates with good crystallinity, regular morphology, and high reactivity. This provides a foundation for the subsequent preparation of lithium manganese iron phosphate precursors.
[0135] In some embodiments of the present invention, the temperature of the second coprecipitation treatment is 40~90°C and the time is 1~6h.
[0136] In detail, the temperature of the second coprecipitation treatment includes, but is not limited to, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or any combination thereof. The time includes, but is not limited to, 1h, 2h, 3h, 4h, 5h, 6h, or any combination thereof.
[0137] By precisely controlling the temperature of the second coprecipitation treatment within the range of 40~90℃ and the time within the range of 1~6h, the coprecipitation kinetics of manganese and iron ions with the intermediate can be effectively regulated. This avoids incomplete reaction and element segregation caused by excessively low temperature, as well as grain coarsening and agglomeration caused by excessively high temperature. It ensures that manganese and iron elements are deposited on the surface of the intermediate in a highly uniform atomic-level mixture, thereby forming a lithium manganese iron phosphate precursor with uniform composition and stable structure.
[0138] In some embodiments of the present invention, the molar ratio of lithium source to first phosphorus source is (2~3):1.
[0139] In detail, the molar ratio of the lithium source and the first phosphorus source includes, but is not limited to, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, or any combination thereof.
[0140] By controlling the molar ratio of lithium source to first phosphorus source within the range of (2~3):1, this invention can effectively regulate the lithium-phosphorus stoichiometry and crystal structure of intermediates, thereby forming lithium-rich or near-stoichiometric intermediates.
[0141] In some embodiments of the present invention, the molar ratio of the metal salt to the second phosphorus source is (1.5~2):1; the metal salt includes a manganese source and an iron source.
[0142] In detail, the molar ratio of the metal salt to the second phosphorus source includes, but is not limited to, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, or any combination thereof.
[0143] This invention controls the molar ratio of metal salts (manganese and iron sources) to a second phosphorus source within the range of (1.5~2):1, ensuring a sufficient excess of phosphorus in the second co-precipitation process. This effectively promotes the complete co-precipitation of manganese, iron, and phosphate ions, avoiding incomplete precipitation of metal ions or the formation of non-target impurities due to insufficient phosphorus source. This improves the purity and chemical homogeneity of the lithium manganese iron phosphate precursor, thereby enhancing the specific capacity and structural stability of the cathode active material.
[0144] In some embodiments of the present invention, the molar ratio of manganese source to iron source is (7:3) to (5:5).
[0145] In detail, the molar ratio of manganese source and iron source includes, but is not limited to, 7:3, 6.5:3.5, 6:4, 5.5:4.5, 5:5 or any combination thereof.
[0146] It is understandable that, in some embodiments, ferrous manganese sulfate can be used as both a manganese source and an iron source. In this case, the molar ratio of manganese to iron in ferrous manganese sulfate is the molar ratio of the manganese source to the iron source.
[0147] When the manganese-iron molar ratio is within the above range, it helps to form a stable lithium manganese iron phosphate precursor during the two-step co-precipitation process, avoiding the formation of manganese-rich or iron-rich phases. At the same time, by adjusting the molar ratio of manganese and iron sources during the preparation process, the manganese-iron ratio in various substances in the lithium manganese iron phosphate precursor can be controlled, thereby ensuring a highly uniform composition distribution of the final cathode active material within the particles and between batches, significantly improving the stability and uniformity of the cathode active material.
[0148] It should be noted that the molar ratio of the manganese source and the iron source added during the preparation process will simultaneously affect the various types of manganese-iron-hydrogen phosphate hydrates and the manganese-iron ratio in the manganese-hydrogen phosphate active material.
[0149] For example, when the molar ratio of manganese source to iron source is 5:5 during the preparation process, if Fe is simultaneously generated in the product... a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y HPO4•cH2O and (Fe e Mn f If HPO4, then a:b is 5:5, x:y is 5:5, and e:f is 5:5.
[0150] In another aspect, the present invention provides a positive electrode active material, which is prepared using the lithium manganese iron phosphate precursor as described above;
[0151] Alternatively, it can be prepared using the lithium manganese iron phosphate precursor obtained by the preparation method described above.
[0152] The positive electrode active material provided by this invention is prepared using the aforementioned lithium manganese iron phosphate precursor. Its internal elemental distribution achieves atomic-level uniform mixing, resulting in a complete crystal structure with few defects and regular particle morphology and uniform size. When this positive electrode active material is used in a positive electrode sheet, it exhibits a high ion diffusion coefficient and a stable charge-discharge platform, leading to higher charge-discharge efficiency and longer cycle life in the battery.
[0153] In some embodiments of the present invention, a detection method including the following steps is used to detect the powder resistivity, 0.1C discharge capacity, and 1C discharge capacity of the positive electrode active material:
[0154] After the positive electrode active material is fabricated into a positive electrode sheet, it is assembled with a negative electrode sheet, electrolyte, and separator according to the following method to obtain a coin cell. The method includes:
[0155] Each positive electrode active material was mixed with conductive carbon black (SP) and PVDF in a weight ratio of 80%:10%:10%, and dispersed to obtain a positive electrode slurry. This slurry was then coated onto an aluminum foil current collector and rolled to obtain an electrode with an areal density of 2 g / cm³. 2 The positive electrode is then punched into a small disc with a diameter of 12mm using a film punch. After drying and weighing, the disc is assembled into a coin cell using a 2025 coin cell case, a Li metal disc as the negative electrode, and conventional high-voltage lithium cobalt oxide electrolyte in a glove box under an Ar protective atmosphere.
[0156] The battery was placed at room temperature (25°C) and charged to 4.3V at a rate of 1 / 3C. Then, it underwent constant voltage charging with a cutoff current rate of 0.05C to obtain a 100% SOC battery. After resting for 10 minutes (as the start of the cycle), it was discharged at a constant current rate of 1 / 3C to a capacity of 0.1C. After resting for 60 minutes, the initial voltage at the last second of the resting period was recorded as V0. Then, it was discharged at a constant current rate of 1.5C for 30 seconds, and the final voltage at the last second of the discharge was recorded as V1. After resting for 10 minutes, it was charged at a constant current rate of 1 / 3C to a capacity of 0.0125C (as the end of the cycle). The DC internal resistance is then (V0-V1) / (1.5C). Nine cycles were performed from the start to the end of the cycle. From the first to the ninth cycle, the obtained DCIR values correspond to 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, and 10% SOC of the battery, respectively.
[0157] The coin cell battery was charged at a constant current rate of 0.1C until the voltage reached 4.3V, then charged at a constant voltage rate until the current was less than or equal to 0.05C, and finally discharged at a constant current rate of 0.1C until the voltage reached 2.2V. The 0.1C discharge specific capacity of the battery was calculated based on the test data. Similarly, the battery was charged and discharged at a constant current rate of 1C, and the corresponding 1C discharge specific capacity was calculated based on the test data.
[0158] Testing revealed that the powder resistivity of the positive electrode active material provided by this invention is <50Ω·cm, the 0.1C discharge capacity is >150mAh / g, and the 1C discharge capacity is >140mAh / g.
[0159] In some embodiments of the present invention, the chemical formula of the positive electrode active material is: Li x (Fe a Mn b ) y PO4, where a:b=1:9~9:1, x=Li / P=1.01~1.06, y=(Fe+Mn) / P=0.955~0.985.
[0160] In some embodiments of the present invention, the powder compaction density of the positive electrode active material is >2.2 g / cm³. 3 .
[0161] The compaction density of the positive electrode active material can be tested by referring to the Chinese national standard GB / T 44330-2024 "Determination of compacted density of positive electrode material powder".
[0162] Specifically, the powder compaction density of the positive electrode active material includes, but is not limited to, 2.21 g / cm³. 3 2.25g / cm 3 2.3g / cm 3 2.35g / cm 3 2.4g / cm 3 2.45g / cm 3 2.5g / cm 3 Or any other >2.2g / cm 3 The range.
[0163] A high compaction density (greater than 2.2 g / cm³) in the positive electrode active material directly reflects a narrow particle size distribution and low porosity. During battery electrode fabrication, more active material can be packed into a unit volume, significantly increasing the electrode's compaction density and volumetric energy density. Simultaneously, a high compaction density improves powder flowability and electrode coating uniformity, reducing the amount of binder and conductive agent required. This not only lowers production costs but also contributes to a more robust electrode structure, thereby enhancing the battery's cycle stability and rate performance.
[0164] In some embodiments of the present invention, the specific surface area of the positive electrode active material is 10~25m². 2 / g.
[0165] The specific surface area of positive electrode active materials can be detected using common methods, such as nitrogen adsorption-desorption.
[0166] Specifically, the specific surface area of the positive electrode active material includes, but is not limited to, 10 m². 2 / g、12 m 2 / g、14 m 2 / g, 16m 2 / g、18 m 2 / g、20 m 2 / g、22 m 2 / g、24 m 2 / g、25 m 2 / g or a range consisting of any two of them.
[0167] When the specific surface area of the positive electrode active material is within the above range, it ensures that the material and the electrolyte have sufficient contact interface, which is conducive to the rapid insertion and extraction of lithium ions, thereby ensuring excellent rate performance and high and low temperature performance. On the other hand, it effectively controls the surface activity of the material, significantly reduces side reactions with the electrolyte, reduces the first irreversible capacity loss, and suppresses gas generation during charging and discharging, thereby improving the safety and cycle life of the battery.
[0168] In some embodiments of the present invention, the positive electrode active material includes a lithium manganese iron phosphate core and a carbon coating layer covering at least a portion of the surface of the lithium manganese iron phosphate core; the carbon coating layer has a mass percentage content of 1% to 2% based on the mass of the positive electrode active material.
[0169] In detail, the mass percentage of the carbon coating includes, but is not limited to, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, or any combination thereof.
[0170] This invention does not limit the preparation method of the positive electrode active material; the positive electrode active material can be prepared using common preparation methods in the art.
[0171] In some embodiments of the present invention, the positive electrode active material is prepared by a preparation method including the following steps:
[0172] 1) The lithium manganese iron phosphate precursor was mixed with a carbon source and then wet-milled to obtain a milling slurry with a Dv50 of 0.1~1μm;
[0173] 2) Spray dry the sand-milled slurry to obtain a spray product with a Dv50 of 1~20μm;
[0174] 3) The sprayed product is sintered at high temperature to obtain lithium manganese iron phosphate cathode.
[0175] The wet sand milling process conditions are as follows: the solid content of the slurry prepared from lithium manganese iron phosphate precursor, carbon source, and pure water is 40%; the sand milling process temperature is controlled at ≤35℃; the sand milling is divided into coarse milling and fine milling; during coarse milling, the diameter of the zirconia beads is 0.6~1.0mm, and the output particle size D50 is controlled at 1~2μm; during fine milling, the diameter of the zirconia beads is 0.2~0.4mm, and the output particle size D50 is controlled at 0.1~0.4μm. The spray drying process conditions are as follows: when feeding the slurry after sand milling, the temperature is controlled at ≤35℃. The inlet air temperature is 200℃~300℃, and the exhaust air temperature is 75℃~110℃. The particle size of the sprayed product is controlled at 1~20μm. The high-temperature sintering process conditions are as follows: the heat treatment is carried out in an inert atmosphere, including two heating stages and a holding stage. In the first stage, the temperature is increased to 300℃~400℃ at a rate of 0.4~1.6℃ / min and held for 0~3h. In the second stage, the temperature is increased to 600℃~800℃ at a certain rate and held for 5~20h. The heating rate in the second stage is not defined and can be reasonable.
[0176] In another aspect, the present invention provides a positive electrode sheet, including a positive electrode active layer, wherein the positive electrode active material includes the positive electrode active material as described above.
[0177] The positive electrode sheet provided by the present invention includes a positive current collector and a positive active layer disposed on at least one side of the positive current collector, wherein the positive active layer includes the aforementioned positive active material.
[0178] Since the positive electrode provided by the present invention includes the above-mentioned positive electrode active material, the positive electrode exhibits higher charge and discharge efficiency and longer cycle life in the battery.
[0179] In the specific preparation of the positive electrode sheet, for example, the above-mentioned positive electrode active material, conductive agent and binder can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and thoroughly stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is uniformly coated on the positive electrode current collector, and after drying, rolling and cutting, the positive electrode sheet is obtained.
[0180] In one specific embodiment, the positive electrode active layer comprises, by weight percentage, 70-99 wt% of positive electrode active material, 0.5-15 wt% of conductive agent, and 0.5-15 wt% of binder; more specifically, it comprises 80-98 wt% of positive electrode active material, 1-10 wt% of conductive agent, and 1-10 wt% of binder.
[0181] The positive current collector can be made of at least one of aluminum foil or nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; and the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane.
[0182] In another aspect, the present invention provides a battery comprising the positive electrode sheet as described above.
[0183] It is conceivable that the battery provided by the present invention, in addition to the aforementioned positive electrode, also includes a negative electrode, an electrolyte, and a separator.
[0184] This invention does not strictly limit the negative electrode active material in the negative electrode sheet. It can be at least one of the commonly used negative electrode active materials, such as graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon suboxide and silicon-carbon negative electrode), and tin-based negative electrode materials (mainly including tin and tin alloy).
[0185] This invention does not strictly limit the choice of electrolyte, and may include one or more of the solvents commonly used in electrolytes, as well as the lithium salts commonly used in electrolytes. For example, the solvent may be ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the lithium salt may be one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0186] This invention does not strictly limit the choice of separator material. It can be one of the separator materials commonly used in batteries, such as polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polyimide electrospun separator (PI), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), cellulose nonwoven separator, and separator with ceramic coating.
[0187] In battery manufacturing, the positive electrode, separator, and negative electrode are wound or stacked to obtain a bare battery, which is then packaged into a pre-stamped aluminum-plastic film bag or steel casing. After the packaged battery is dried at 85°C, the electrolyte is injected into the dried battery. The battery undergoes resting, formation, and secondary sealing to complete battery manufacturing.
[0188] The battery provided by this invention includes the aforementioned positive electrode, and therefore possesses excellent ion-electron conductivity, rate performance, and energy density. Specifically, the battery maintains stable capacity output under high-rate charge-discharge conditions and exhibits a low capacity decay rate during long-term cycling.
[0189] The lithium manganese iron phosphate precursor provided by the present invention will be described in detail below through specific embodiments.
[0190] Example 1
[0191] The method for preparing the lithium manganese iron phosphate precursor provided in this embodiment includes the following steps:
[0192] 1. Add 10% pure water to the reactor, which is the total volume of the reactor. Pump 2.5 mol / L lithium sulfate and 85% concentrated phosphoric acid (first phosphorus source) into the reactor, ensuring that the molar ratio of Li salt and first phosphorus source pumped into the reactor per unit time is 2.95:1. To ensure that Li / P > 1, add an additional amount of lithium carbonate. At the same time, add 10 mol / L sodium hydroxide solution and ensure that the pH in the reactor is 5. After feeding, the first mixed system is obtained, and the solid content of the first mixed system is 15%. Heat to 90℃ and perform the first co-precipitation treatment for 1 hour to obtain slurry A including intermediates.
[0193] 2. In the above slurry A, 2 mol / L ferrous manganese sulfate, 5% dilute phosphoric acid, and 1 mol / L sodium hydroxide with a manganese-to-iron ratio of 6:4 are pumped into the reactor, ensuring that the molar ratio of ferrous manganese sulfate to phosphoric acid pumped into the reactor per unit time is 1.5:1, to obtain a second mixed system with a solid content of 5%. The mixture is then subjected to a second co-precipitation treatment at 80℃ for 6 hours while maintaining pH=4. After washing and drying, the lithium manganese iron phosphate precursor is obtained.
[0194] Example 2
[0195] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0196] In step 1), the pH of the first mixed system is 11. In step 2), the manganese-iron ratio of the ferrous manganese sulfate pumped in is 4:6.
[0197] Example 3
[0198] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0199] In step 2), the manganese-iron ratio of ferrous manganese sulfate pumped in is 5:5. Then, the pH is gradually increased from 4 to 7.
[0200] Example 4
[0201] The method for preparing the lithium manganese iron phosphate precursor provided in this embodiment includes the following steps:
[0202] 1. Add 10% pure water to the reactor, which is the total volume of the reactor. Pump 2.5 mol / L lithium sulfate and 85% concentrated phosphoric acid (first phosphorus source) into the reactor, ensuring that the molar ratio of Li salt to phosphorus source pumped into the reactor per unit time is 2:1. At the same time, add 10 mol / L sodium hydroxide solution and ensure that the pH in the reactor is 7. After the feeding is completed, the first mixed system is obtained, and the solid content of the first mixed system is 15%. Heat to 40℃ and perform the first co-precipitation treatment for 6 hours to obtain slurry A including intermediates.
[0203] 2. In the above slurry A, 2 mol / L ferrous manganese sulfate, 5% dilute phosphoric acid, and 1 mol / L sodium hydroxide with a manganese-to-iron ratio of 1:9 are pumped in to ensure that the molar ratio of ferrous manganese sulfate and phosphoric acid pumped into the reactor per unit time is 2:1, thus obtaining a second mixed system. The solid content of the second mixed system is 15%. The pH is kept at 90℃ for a second co-precipitation treatment for 1 hour. After washing and drying, the lithium manganese iron phosphate precursor is obtained.
[0204] Example 5
[0205] The method for preparing the lithium manganese iron phosphate precursor provided in this embodiment includes the following steps:
[0206] 1. Add 10% pure water to the reactor, which is the total volume of the reactor. Pump 2.5 mol / L lithium sulfate and 85% concentrated phosphoric acid (first phosphorus source) into the reactor, ensuring that the molar ratio of Li salt to phosphorus source pumped into the reactor per unit time is 2.5:1. At the same time, add 10 mol / L sodium hydroxide solution and ensure that the pH in the reactor is 9. After the feeding is completed, the first mixed system is obtained, and the solid content of the first mixed system is 30%. Heat to 70℃ and perform the first co-precipitation treatment for 3 hours to obtain slurry A including intermediates.
[0207] 2. In the above slurry A, 2 mol / L ferrous manganese sulfate, 5% dilute phosphoric acid, and 1 mol / L sodium hydroxide with a manganese-to-iron ratio of 9:1 are pumped into the reactor to ensure that the molar ratio of ferrous manganese sulfate to phosphoric acid pumped into the reactor per unit time is 1.75:1, resulting in a second mixed system with a solid content of 5%. The mixture is then subjected to a second co-precipitation treatment at 75℃ for 3 hours, maintaining pH=9. After washing and drying, the lithium manganese iron phosphate precursor is obtained.
[0208] Example 6
[0209] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0210] In step 1), the pH of the first coprecipitation treatment is 4.5.
[0211] Example 7
[0212] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0213] In step 2), the pH of the second coprecipitation treatment is 10.
[0214] Example 8
[0215] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0216] In step 1), the temperature of the first coprecipitation treatment is 95℃ and the time is 7h.
[0217] Example 9
[0218] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0219] In step 2), the temperature of the second coprecipitation treatment is 35°C and the time is 7 hours.
[0220] Example 10
[0221] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0222] In step 1), the molar ratio of lithium source to first phosphorus source is 3.2:1.
[0223] Example 11
[0224] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0225] In step 2), the molar ratio of the metal salt to the second phosphorus source is 2.5:1.
[0226] Example 12
[0227] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0228] In step 1), the solid content of the first mixture is 10%.
[0229] Example 13
[0230] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0231] In step 1), the solid content of the first mixture is 35%.
[0232] Example 14
[0233] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0234] In step 2), the solid content of the second mixture is 3%.
[0235] Example 15
[0236] The preparation method of the lithium manganese iron phosphate precursor provided in this embodiment is basically the same as that in Example 1, except that:
[0237] In step 2), the solid content of the second mixture is 20%.
[0238] Comparative Example 1
[0239] The method for preparing the lithium manganese iron phosphate precursor provided in this comparative example includes the following steps:
[0240] Add 10% pure water to the reactor, which is the total volume of the reactor. Pump 2.5 mol / L lithium sulfate, 2 mol / L ferrous manganese sulfate (manganese to iron ratio of 6:4), and 85% concentrated phosphoric acid (first phosphorus source) into the reactor, ensuring that the molar ratio of Li salt, phosphorus source, iron source, and manganese source pumped into the reactor per unit time is 1:1. At the same time, add 10 mol / L sodium hydroxide solution and ensure that the pH in the reactor is 5 and the temperature is 90℃. After feeding, age for 1 hour, wash and dry to obtain lithium manganese iron phosphate precursor.
[0241] Test case
[0242] 1. Material composition test
[0243] The composition of various substances in the lithium manganese iron phosphate precursor was tested using XRD, including the following steps:
[0244] The lithium manganese iron phosphate precursors provided in each embodiment and comparative example were ground to a uniform particle size to avoid particle effects. Samples were prepared using a tableting method, with samples containing water of crystallization handled in a dry environment to prevent moisture loss.
[0245] The XRD parameters were set as follows: X-ray source: Cu Kα target (wavelength 0.15418 nm), voltage 40 kV, current 15 mA. Scanning parameters: 2θ range 10º~90º, step size 0.02º, speed 5~10º / min. Ensure the sample surface is perpendicular to the X-ray beam and optimize the optical path (e.g., using a BBHD module to improve sensitivity).
[0246] Preheat the instrument for 30 minutes to stabilize the X-ray tube. Load the sample into the center of the sample stage, ensuring it is flat and tilt-free. After setting the parameters, start the test and record the raw data (.raw or .xrdml format).
[0247] Background removal and curve smoothing (using software such as Jade / HighScore). Compare with a standard PDF library to identify Li3PO4 and (Fe2+) compounds. a Mn b Characteristic peaks such as 5H2(PO4)4•4H2O were observed to obtain the XRD curve, and the amount of water of crystallization was then calculated by fitting the relationship between the elements.
[0248] in Figure 1 The XRD curve of the lithium manganese iron phosphate precursor provided in Example 1 of this invention. Figure 1 As can be seen, the phase composition of the lithium manganese iron phosphate precursor provided in Example 1 of the present invention includes Li3PO4, (Mn,Fe)5H2(PO4)4•4H2O, and MnHPO4•2.25H2O; Figure 2 The XRD curve of the lithium manganese iron phosphate precursor provided in Comparative Example 1 of this invention is obtained by... Figure 2 As can be seen, the lithium manganese iron phosphate precursor prepared in Comparative Example 1 is basically consistent with the standard diffraction card (JCPDS No. 011-0379) of (Mn,Fe)5H2(PO4)4•4H2O; however, no diffraction peak matching Li3PO4 was found. This indicates that under the conditions of simultaneous feeding in Comparative Example 1, lithium phosphate itself has a relatively large solubility product constant (Ksp), resulting in a low precipitation rate and difficulty in complete precipitation. Simultaneously, in the coexisting ion system, the solubility product constants of ferrous phosphate and manganese phosphate are much smaller than those of lithium phosphate. According to the thermodynamic trend of precipitation transformation, ferrous phosphate and manganese phosphate will preferentially form and precipitate in large quantities, thereby competing for and consuming phosphate ions in the solution. Constrained by these two factors, the formation of lithium phosphate is significantly inhibited, and no lithium phosphate phase is detected in the final product.
[0249] 2. Detect the proportion of various elements
[0250] According to the national standard GB / T 46512-2025 "Lithium Manganese Iron Phosphate", inductively coupled plasma atomic emission spectrometry (ICP-AES) was used to test the mass percentages of Fe, Mn, P, and Li in the lithium manganese iron phosphate precursor, thereby obtaining Mn / Fe, Li / P, and (Mn+Fe) / P. Combined with XRD detection, the mass percentages of Li3PO4 and (Fe2+Fe2+)P were calculated and determined. a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y HPO4•cH2O, (Fe e Mnf The molar ratio of HPO4. For example, using inductively coupled plasma atomic emission spectrometry, the mass percentages of Fe, Mn, P, and Li were measured to be 12.77%, 18.85%, 18.38%, and 4.24%, respectively. From this, we can confirm that Mn / Fe = 6:4, (Mn+Fe) / P = 0.964, and Li / P = 1.029, further confirming a:b = x:y = 4:6. According to XRD, c = 2.25. Through fitting calculations, the molar ratios of Li3PO4 and (Fe...) are... 0.4 Mn 0.6 )5H2(PO4)4•4H2O、(Fe 0.4 Mn 0.6 HPO4•2.25H2O, (Fe e Mn f The molar percentage of HPO4 is 48:40:12:0.
[0251] The test results are shown in Table 1.
[0252] Table 1
[0253]
[0254] 3. Loose packing density and compacted density
[0255] According to the national standard GB / T 1479.1-2011 "Metal Powders - Determination of Bulk Density - Part 1: Funnel Method", the bulk density (A g / cm³) of lithium manganese iron phosphate precursor was tested. 3 ).
[0256] According to the national standard GB / T 5162-2021 "Determination of Tap Density of Metal Powders", the tap density (B g / cm³) of lithium manganese iron phosphate precursor was tested. 3 ).
[0257] The test results are shown in Table 2.
[0258] 4. Morphology, average width of cross-section, and average length
[0259] The morphology and size of the lithium manganese iron phosphate precursor were characterized using scanning electron microscopy.
[0260] First, a trace amount of precursor powder was sprayed onto conductive adhesive, and after gold sputtering, the sample was placed in the sample chamber of a scanning electron microscope and observed under an accelerating voltage of 5-15 kV.
[0261] By adjusting the magnification, after observing the overall particle distribution under low magnification, focus on well-dispersed individual particles under high magnification (typically 30,000-100,000x). The precursor exhibits a regular prismatic morphology, with some particles displaying complete columnar geometry and others exposing their cross-sections. For accurate size measurement, at least 50 well-defined individual particles are selected and calibrated and measured using image analysis software (such as ImageJ): for particles with visible cross-sections, the diameter of their circumscribed circle or the perpendicular distance between opposite sides is measured as the cross-sectional width, and the average value is taken; for particles lying flat or appropriately oriented, their maximum dimension along the long axis is measured as the length, and the average value is taken.
[0262] Statistical measurements show that all particle sizes are concentrated, and the precursor has a uniform nanoprismatic morphology.
[0263] The test results are shown in Table 2.
[0264] in Figure 3 This is a scanning electron microscope (SEM) image of the lithium manganese iron phosphate precursor provided in Embodiment 1 of the present invention. Figure 3 As can be seen, the lithium manganese iron phosphate precursor provided in Example 1 exhibits a prismatic morphology with an average length of approximately 475 nm and an average cross-sectional width of approximately 275 nm.
[0265] Figure 4 This is a scanning electron microscope (SEM) image of the lithium manganese iron phosphate precursor provided in Comparative Example 1 of the present invention. Figure 4 It can be seen that the lithium manganese iron phosphate precursor prepared in Comparative Example 1 has a plate-like morphology.
[0266] 5. Specific surface area
[0267] The specific surface area (BET, m) of lithium manganese iron phosphate precursor was determined according to GB / T 19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method". 2 / g).
[0268] The test results are shown in Table 2.
[0269] 6. Loose packing density of intermediates
[0270] According to the national standard GB / T 1479.1-2011 "Determination of the apparent density of metal powders - Part 1: Funnel method", the apparent density (C g / cm³) of the lithium manganese iron phosphate precursor intermediate was tested. 3 ).
[0271] The test results are shown in Table 2.
[0272] Table 2
[0273]
[0274] 7. Performance testing of positive electrode active materials
[0275] The lithium manganese iron phosphate precursors provided in the examples and comparative examples were sequentially prepared into positive electrode active materials, including the following steps:
[0276] The lithium manganese iron phosphate precursor, 5% glucose and 7% polyethylene glycol were mixed evenly and wet-milled to a D50 of 0.4 μm. Then, the mixture was spray-dried and heat-treated under a nitrogen atmosphere. The temperature was increased to 300℃ at 0.4℃ / min and held for 3 hours. Then, the temperature was increased to 600℃ at 2℃ / min and held for 10 hours. Finally, the positive electrode active material was obtained by air jet milling.
[0277] (1) XRD detection
[0278] The composition of various substances in the positive electrode active material is tested using XRD, including the following steps:
[0279] The positive electrode active materials provided in each embodiment and comparative example are ground to a uniform particle size to avoid particle effects. Samples are prepared using a tableting method; samples containing water of crystallization must be handled in a dry environment to prevent moisture loss.
[0280] The XRD parameters were set as follows: X-ray source: Cu Kα target (wavelength 0.15418 nm), voltage 40 kV, current 15 mA. Scanning parameters: 2θ range 10º~90º, step size 0.02º, speed 5~10º / min. Ensure the sample surface is perpendicular to the X-ray beam and optimize the optical path (e.g., using a BBHD module to improve sensitivity).
[0281] Preheat the instrument for 30 minutes to stabilize the X-ray tube. Load the sample into the center of the sample stage, ensuring it is flat and tilt-free. After setting the parameters, start the test and record the raw data (.raw or .xrdml format).
[0282] Background removal and curve smoothing (using software such as Jade / HighScore). Compare with a standard PDF library to identify Li3PO4 and (Fe2+) compounds. a Mn b Characteristic peaks such as 5H2(PO4)4•4H2O were observed to obtain the XRD curve.
[0283] in, Figure 5 The XRD pattern of the positive electrode active material prepared from the lithium manganese iron phosphate precursor provided in Example 1 of this invention is shown below. Figure 5 It can be seen that its phase composition is LiFe a Mn bBecause Fe and Mn have similar atomic radii, the XRD patterns of LiFePO4 and LiMnPO4 highly overlap, with their diffraction peak positions essentially matching. Therefore, when performing phase retrieval on the XRD pattern of this cathode material, both LiFePO4 and LiMnPO4 phases were simultaneously matched.
[0284] (2) Scanning electron microscopy detection
[0285] The scanning electron microscope (SEM) examination of the positive electrode active material includes the following steps:
[0286] First, the positive electrode active material powder is evenly dispersed on conductive tape, or it is made into an electrode sheet and then cut to a suitable size to ensure that the sample surface is flat and has good conductivity. If necessary, gold or carbon spraying treatment is required to enhance conductivity.
[0287] Next, the prepared sample is placed in the scanning electron microscope sample chamber and evacuated to the required working pressure. Then, it is observed under appropriate accelerating voltage (usually 5-20 kV) and beam current conditions. The morphology, particle size distribution, and agglomeration state of the material are analyzed step by step by adjusting the magnification from low to high.
[0288] Finally, images and data are recorded and saved, and morphological characteristics are comprehensively evaluated in conjunction with material properties, such as the observation of defects like particle uniformity, surface roughness, or cracks, in order to correlate them with their electrochemical behavior.
[0289] Figure 6 This is a SEM image of the positive electrode active material prepared from the lithium manganese iron phosphate precursor provided in Example 1 of the present invention. Figure 6 As can be seen, the positive electrode active material exhibits a near-spherical shape, with primary particle diameters ranging from 100 nm to 400 nm and secondary sphere diameters around 15 μm. The primary particle diameter is determined by the sand milling process before sintering; sand milling to nanoscale particle size helps shorten the lithium-ion diffusion path and increase the diffusion rate. The secondary sphere diameter and spherical morphology are inherited from the spray drying process after sand milling, and are consistent with the morphology and particle size of the sprayed particles.
[0290] (3) Compacted density
[0291] The compaction density of the positive electrode active materials provided in all examples and comparative examples was determined in accordance with GB / T 44330-2024 "Determination of compaction density of positive electrode material powder for lithium-ion batteries".
[0292] The test results are shown in Table 3.
[0293] (4) Specific surface area
[0294] The specific surface area of the positive electrode active material was determined according to GB / T 19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method".
[0295] The test results are shown in Table 3.
[0296] (5) Percentage of carbon layer mass
[0297] The mass percentage of carbon layer in the positive electrode active material was determined according to YS / T 1028.4-2015 "Chemical Analysis Methods for Lithium Iron Phosphate - Part 4: Determination of Carbon Content - High-Frequency Combustion Infrared Absorption Method", including the following steps:
[0298] Accurately weigh an appropriate amount of sample and flux together and place them in a high-frequency induction furnace, and set the instrument atmosphere to flowing oxygen.
[0299] When heated to a high temperature (1400℃~1700℃) in an oxygen atmosphere, the carbon layer reacts with oxygen to produce carbon dioxide.
[0300] When carbon dioxide gas is introduced into an infrared detection cell, carbon dioxide can absorb infrared light of a specific wavelength, and the intensity of absorption is directly proportional to its concentration.
[0301] The carbon-sulfur analyzer automatically calculates the mass fraction of carbon in the sample by detecting the degree of infrared light absorption. The test results are shown in Table 3.
[0302] (6) Powder resistivity
[0303] The powder resistivity of the cathode active material was tested according to GB / T 30835-2014 "Carbon Composite Lithium Iron Phosphate Cathode Material for Lithium-ion Batteries".
[0304] The test results are shown in Table 3.
[0305] Table 3
[0306]
[0307] 8. Electrochemical performance testing
[0308] After the positive electrode active materials of the examples and comparative examples were respectively fabricated into positive electrode sheets, they were assembled with negative electrode sheets, electrolytes, and separators according to the following method to obtain coin cells. The method includes:
[0309] Each positive electrode active material was mixed with conductive carbon black (SP) and PVDF in a weight ratio of 80%:10%:10%, and dispersed to obtain a positive electrode slurry. This slurry was then coated onto an aluminum foil current collector and rolled to obtain an electrode with an areal density of 2 g / cm³. 2 The positive electrode is then punched into a small disc with a diameter of 12mm using a film punch. After drying and weighing, the disc is assembled into a coin cell using a 2025 coin cell case, a Li metal disc as the negative electrode, and conventional high-voltage lithium cobalt oxide electrolyte in a glove box under an Ar protective atmosphere.
[0310] (1) Discharge specific capacity test
[0311] The mold battery was charged at a constant current of 0.1C to 4.3V, charged at a constant voltage to 0.05C to cut off charging, and then discharged at a constant current of 0.1C to 2.2V; the 0.1C discharge specific capacity of the battery was calculated based on the test data.
[0312] Similar to the above test method, the battery was charged and constant current was used at 1C, and the 1C discharge specific capacity of the battery was calculated based on the test data.
[0313] The test results are shown in Table 4.
[0314] Table 4
[0315]
[0316] As shown in Table 4, the positive electrode active material prepared from the lithium manganese iron phosphate precursor provided in this embodiment of the invention has a lower powder resistivity compared to the positive electrode active material prepared from the precursor provided in the comparative example. When used in a battery, it exhibits higher 0.1C discharge specific capacity and 1C discharge specific capacity. This indicates that the positive electrode active material has superior compaction density and volumetric energy density.
[0317] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A lithium manganese iron phosphate precursor, characterized in that, Including lithium phosphate and iron manganese hydrogen phosphate hydrate.
2. The lithium manganese iron phosphate precursor according to claim 1, characterized in that, The ferric manganese hydrogen phosphate hydrate includes (Fe a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y At least one of HPO4•cH2O, wherein a:b is 1:9~9:1, x:y is 1:9~9:1, and 0<c≤3.
3. The lithium manganese iron phosphate precursor according to claim 1, characterized in that, The lithium manganese iron phosphate precursor also includes iron manganese hydrogen phosphate, the chemical formula of which is (Fe e Mn f HPO4, where e:f is 1:9 to 9:
1.
4. The lithium manganese iron phosphate precursor according to claim 1 or 2, characterized in that, The loose pack density of the lithium manganese iron phosphate precursor is A, 0.8 g / cm³. 3 ≤A≤1.5g / cm 3 ; And / or, the tap density of the lithium manganese iron phosphate precursor is B, 1.5 g / cm³. 3 ≤B≤2.5g / cm 3 .
5. The lithium manganese iron phosphate precursor according to claim 2, characterized in that, The lithium manganese iron phosphate precursor includes lithium phosphate, (Fe) a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y HPO4•cH2O, a:b is 1:9~9:1, x:y is 1:9~9:1, 0<c≤3; The lithium phosphate, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe x Mn y The molar ratio of HPO4•cH2O is (1.5~56):(2~48):(0.1~96.5).
6. The lithium manganese iron phosphate precursor according to claim 3, characterized in that, The lithium manganese iron phosphate precursor includes lithium phosphate, (Fe) a Mn b )5H2(PO4)4•4H2O、(Fe e Mn f HPO4, a:b ratio is 1:9 to 9:1, e:f ratio is 1:9 to 9:1; The lithium phosphate, (Fe a Mn b )5H2(PO4)4•4H2O、(Fe e Mn f The molar ratio of HPO4 is (1.5~56):(2~48):(0.1~96.5).
7. The lithium manganese iron phosphate precursor according to any one of claims 1-6, characterized in that, The lithium manganese iron phosphate precursor is prismatic in shape, and the average width of the cross section of the lithium manganese iron phosphate precursor is 100~500nm; the average length of the lithium manganese iron phosphate precursor is 100~1000nm. And / or, the specific surface area of the lithium manganese iron phosphate precursor is ≤20m². 2 / g.
8. The lithium manganese iron phosphate precursor according to any one of claims 1-7, characterized in that, In the lithium manganese iron phosphate precursor, the (Mn+Fe) / P ratio is (0.955~0.985):1, and the Li / P ratio is (1.01~1.06):
1.
9. A method for preparing the lithium manganese iron phosphate precursor according to any one of claims 1-8, characterized in that, Includes the following steps: 1) The first mixed system, including a lithium source and a first phosphorus source, is subjected to a first coprecipitation treatment to obtain an intermediate; 2) Perform a second coprecipitation treatment on the second mixed system including the intermediate, the second phosphorus source, the manganese source, and the iron source to obtain the lithium manganese iron phosphate precursor.
10. The preparation method according to claim 9, characterized in that, The solid content of the first mixture is 15% to 30%; And / or, the solid content of the second mixture is 5% to 15%; And / or, the pH of the first coprecipitation treatment is 5-8; And / or, the pH of the second coprecipitation treatment is 4 to 9.
11. The preparation method according to claim 9 or 10, characterized in that, The temperature of the first coprecipitation treatment is 40~90℃, and the time is 1~6h; And / or, the temperature of the second coprecipitation treatment is 40~90℃, and the time is 1~6h.
12. The preparation method according to any one of claims 9-11, characterized in that, The molar ratio of the lithium source to the first phosphorus source is (2~3):1; And / or, the molar ratio of the metal salt to the second phosphorus source is (1.5~2):1; the metal salt includes the manganese source and the iron source; And / or, the molar ratio of the manganese source and the iron source is (7:3) to (5:5).
13. A positive electrode active material, characterized in that, It was prepared using the lithium manganese iron phosphate precursor described in claims 1-8; Alternatively, it can be prepared using the preparation method described in any one of claims 9-12, which yields a lithium manganese iron phosphate precursor.
14. A positive electrode plate, characterized in that, It includes a positive electrode active layer, wherein the positive electrode active material includes the positive electrode active material according to claim 13.
15. A battery, characterized in that, Includes the positive electrode sheet as described in claim 14.